Lived Experiences of Karatedo Athletes: A Phenomenological Study - Mortejo, Alonzo (International Martial Arts and Culture Journal, 2024)
Studi Purpose With an emphasis on their motivations, difficulties, and personal development, this study examines the lived experiences of karate dojo athletes at a few Philippine institutions. Method The study examines how Karatedo practice affects athletes' self-discipline, fortitude, and identity using a qualitative phenomenological technique. Important themes, such as intrinsic and extrinsic motivation, physical and psychological challenges, and the transforming impact of Karatedo in creating life skills, surfaced through in-depth interviews with collegiate and national-level athletes from state colleges and universities (SUCs). Results show that Karatedo helps athletes develop their mental toughness, emotional intelligence, and sense of belonging, which in turn affects their career and personal paths.